THE INFLUENCE OF LIQUIDITY, ACTIVITY, AND PROFITABILITY ON DIVIDEND POLICY OF MANUFACTURING COMPANIES IN THE BEI - RIA FEBRIYANTI BR SITEPU; ARGO PUTRA PRIMA (Jurnal Ekonomi, 2022)
For every potential investor who thinks logically and wisely in investing, his attention will be focused and directed at the value or rate of return of a product or investment which is commonly called dividend. The pharmaceutical sub-sector company is the one that has experienced quite good development, especially in the current situation where the demand for drugs and the like has increased sharply due to the COVID-19 outbreak. Of course, this greatly affects the condition of pharmaceutical companies, especially dividend policies. The goal of this investigation is tois to examine the impact of profitability, liquidity, and activity on the dividend policies of pharmaceutical subsector firms from 2016 to 2021. The research approach is quantitatively descriptive, and multiple linear regression is utilized as the analytical instrument. During the study period, the research sample consists of six pharmaceutical subsector enterprises that pay dividends and routinely produce financial reports. A sig t test score of 0.811 indicates that profitability has no influence on dividend policy, while a test value of 0.035 indicates that liquidity and activity both have significant effects, both of which are below the 0.05 minimal limit. 0.02 is less than the minimum criterion for the sig t test.